The Role Of Stability Testing In Determining The Shelf Life And Storage Conditions Of Pharmaceutical Products: A Narrative Review - Najmi Qamariah Tomayahu; Nur Amaliah Abdullah; Nabila Pricilia Pakaya; Sri Meylan H.A Baruadi; Nur Ain Thomas; Faradila Ratu Cindana Mo'o (International Journal of Health Engineering and Technology, 2026)
Stability testing plays an important role in determining the shelf life and appropriate storage conditions of pharmaceutical products. This narrative review aimed to evaluate the role of Stability testing in maintaining the quality, safety, and effectiveness of pharmaceutical products during storage and distribution. Literature was collected from scientific databases including Google Scholar, PubMed, ScienceDirect, and ResearchGate using keywords related to Stability testing and pharmaceutical storage. The reviewed studies showed that Stability testing, including long-term, accelerated, intermediate, and forced degradation studies, can evaluate physical, chemical, and microbiological changes caused by environmental factors such as temperature, humidity, light, and oxidation. Several studies reported that high temperature and humidity accelerated drug degradation, while appropriate storage conditions maintained product stability within pharmacopeial specifications. Stability data are also essential for determining expiration dates, packaging selection, and storage instructions. Therefore, Stability testing is a crucial scientific approach in the pharmaceutical industry to ensure product quality, regulatory compliance, and patient safety throughout the product shelf life.